Enhancement of secondary radiation flux energy 3.63 % during appearance of Full Moon on October 13, 2022 at Udaipur (Rajasthan), India - Pareek, Devendra; Baregama, Deepali (Nepal Journal of Science and Technology, 2023)
We observed variation of secondary radiation flux energy (SRFE) at Udaipur (27o 43’ 12.00” N, 75o 28’ 48.01” E), Rajasthan, India during Full Moon in month of October, 2022. In this experimental study ground based NaI (Tl) Scintillation detector used. The data files were stored in computer for half hour duration around time 21.00 IST to 21.30 IST on October 6, 9, 10, 11, 12, 13, 14 and 15. The objective in this study is to observe secondary radiation flux energy during Full Moon. Analyzed data reveal significant enhancement of secondary radiation flux energy about 3.63 % on date of full Moon. We interpret such variation of SRFE on the basis of more reflection of solar radiation form surface of Full Moon.